Semiotics Analysis in Tupan Cafe Menus (Lexeme : Journal of Linguistics and Applied Linguistics, 2019)
This study attempts to explain and describe the semiotic process and the message implied in Tupan Cafe menu. Semiotics approach from Pierce is applied to identify and analyze the data which focus on Representament, Object, and Interpretant. The method of this study is descriptive qualitative because the writer collected the data in the form of written words which produces descriptive information. There are six Tupan Cafe menus that were analyzed in this study. Those are the menus;Classic Orange Panacotta, Legendary Volcano & Pitbull, Trilogy Chicken ala Cordon Bleu, Crisp Fried John Dory Cheese, Coffee V60, and Bloody Jean. The writer is interested in analyzing them because those menus have hidden message that sometimes the viewers can not understand the message of menus well. The results of the study showed that all the menus have an aim to persuade the readers to know the meanings of the menus although the signs in each menu are different.